Impact of Built‐In Electric Field on the Emission Characteristics of InAs/GaAs Quantum Dot Laser Structure. Issue 7 (20th May 2021) - Gupta, Nitika; Mudi, Priyabrata; Yelashetty, Arvind; Sharma, Tarun K.; Dhirhe, Devnath
Abstract : The impact of the built‐in electric field on the emission characteristics of an InAs/GaAs quantum dot (QD) laser structure is investigated by performing systematic spectroscopic measurements. Photoluminescence (PL) features related to the ground state (GS) and excited state (ES) transitions of a QD ensemble are clearly observed in the temperature range of 8–300 K. The cross‐sectional transmission electron microscopy image and a systematic analysis of temperature‐dependent PL data confirm the excellent crystalline and optical quality of the QD laser structure. It is found that the values of the activation energy associated with GS and ES transitions of the QD sample reasonably match with the energy splitting of PL features. This successfully explains the trends observed in temperature‐dependent PL spectra, where thermal transfer of carriers to the wetting/barrier layer via QD excited states is proposed to be a major decay channel. An interesting observation is made where the integrated intensity of PL features increases up to 75 K and falls thereafter during the heating cycle. Such a peak‐like behavior of the integrated intensity is explained by invoking the temperature dependence of the built‐in electric field, which is estimated from the analysis of Franz–Keldysh oscillations observed in photoreflectance spectra and is important in the design of QD lasers. Abstract : The impact of the built‐in electric field on the emission characteristics of an InAs/GaAs quantum dot laser structure is investigated. The intensity of photoluminescence features increases at temperature from 8 to 75 K and falls thereafter up to 300 K. This peak‐like behavior is explained by invoking the temperature dependence of the built‐in electric field, estimated from the analysis of Franz–Keldysh oscillations observed in the photoreflectance spectra.